Salt of the earth - Meredith, Stanley; Stark, Leonard; Wilson, Michael 1914-1978; Revueltas, Rosaura 1910-1996; Chacón, Juan 1916-1985; Geer, Will 1902-1978 (Alpha Video, 2004)
A semidocumentary of the year-long struggle by Chicano zinc miners in New Mexico striking against unsafe working conditions. When an injunction is issued against the workers from picketing, the wives take up battle with a fury, leaving the husbands to care for home and children. They finally overcome the forces of the mine owner and the law that backs them up
Orig.: USA, 1954
"Filmmaker approved version"--Container. - Filmed in New Mexico in 1953
Enth. Chronology of the film's production and distribution; production photos; biographies; filmographies; theatrical trailer; editing and shooting notes; a history of the strike the film is based on accompanied by pictures; history of the Hollywood blacklist; Congressional testimony of the blacklisted filmmakers; the documentary "The Hollywood ten" (about blacklisted writers and directors who defied the House Committee on Un-American Activities in 1947 and were imprisoned for contempt of Congress)
Keywords: United States / Congress / House / Committee on Un-American Activities; United States. -- Congress. -- House. -- Committee on Un-American Activities; Strikes and lockouts / Zinc mining / New Mexico / Drama; Miners / Labor unions / New Mexico / Drama; Mexican Americans / New Mexico / Drama; Blacklisting of entertainers / United States; Blacklisting of authors / United States; Gewerkschaft; Strikes and lockouts -- Zinc mining -- New Mexico -- Drama; Miners -- Labor unions -- New Mexico -- Drama; Mexican Americans -- New Mexico -- Drama; Blacklisting of entertainers -- Drama; Historical films.; Populist films.; Feature films.; Social problem films.; Fiction films.; Chicanos; Bergmann; Streik; USA; New Mexico; Film; DVD-Video